Julien Faure rubans et soieries, 1864-2021 - Nadine Besse (In Situ)
The Julien Faure firm is a family enterprise that makes ribbons and silk, now run by members of the family’s fifth generation. It can be seen as an emblem of the Saint-Etienne region where it is located. For 160 years now, it has overcome adversity and still looks to the future to transmit the skills which imprint its identity on the creation, manufacture and selling of its up market products. The firm has opened up its rich collection of textile and administrative archives in order to acquire a better understanding of its own history. These archives are interpreted here in a transhistorical and anthropological vision. This article is an invitation then into the intimacy of the firm’s special culture, which views its own heritage as an asset for production and in which management has always been supported by the staff, all seeing themselves as ‘Julien Faure people’. This particular example proves that the skills we are so afraid of seeing disappear can be preserved and enriched and are handed on primarily by the activities of firms active in the market place and surviving despite crises: firms which dare to change in order to conserve.